TOURISM CARRYING CAPACITY AT PETUNGKRIYONO FOREST AND ITS SUPPORTING AREAS - Ambarwati, Nurwidya (Journal of Environmental Science and Sustainable Development, 2024)
Supported by a variety of diversity and landscapes, the development of tourism in the Petungkriyono area is growing rapidly. Optimizing ecotourism services in the Petungkriyono forest without disrupting the ecosystem and damaging the environment can be done by limiting the number of visitors at tourism sites. This study aims to find out information about the tourism capacity of some tourist attractions in the local forest. This study uses the Cifuentes model to predict the maximum number of visitor capacities that can be accommodated in a tourist attraction called Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC) with management capacity as a consideration. The results of the study show that from PCC calculations, which means a maximum number of visitors physically provided by the space, Curug Bajing has the highest number of visitors (1,365 people) in a day from four other tourist objects. Rogojembangan Coffee Shop has the fewest visitors (347 respondents). The highest number of RCC calculations is Curug Bajing tourist attraction (1,365 respondents), and the lowest is Rogojembangan Coffee Shop (346 respondents). In addition, ECC calculations show that the highest number of visitors is at Curug Bajing (1,364 respondents), and the lowest is at the Rogojembangan Coffee Shop (345 respondents). For the management of tourism, the results can provide insight into which tourist attractions require further development. Regarding the result, it shows that Curug Lawe tourist attraction has an exceeded carrying capacity, so our results provide a basis for local tourism management and stakeholders to develop more effective strategies in tourism in the local forest, such as controlling and managing the tourism area by limiting visitors, managing the facilities, waste management, and avoid the habitat of endemic fauna so that we can maintain forest sustainability while utilizing natural tourism in the Petungkriyono forest.